IMPLEMENTASI PROGRAM KELUARGA BERENCANA (KB) PADA WANITA PASANGAN USIA SUBUR (PUS) DI WILAYAH PESISIR PANTAI DESA BAGAN KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Susilawati Susilawati; Saski Amalia Khairunnisa (CV. ADIBA AISHA AMIRA, 2023)
The Family Planning Program (KB) is a government program designed to balance the needs and population in Indonesia. The family planning program is also carried out for the welfare of the community, especially from an economic and health point of view. Indonesia is one of the countries with the largest population in the world. Based on worldmaters data at the end of 2018, Indonesia has a population of 269 million people, ranking the top four countries with the largest population in the world. The uncontrolled increase in population and the rapid rate of population growth has resulted in an increase in the need for life, while the quality of the environment has decreased. This results in an imbalance between the supply of existing resources and household needs so that life welfare is not fulfilled. Increasing family welfare needs to be considered because the family is the smallest unit in social life so that the family has a role in supporting the success of development. The family plays a major role in forming quality human resources. The family planning program is also carried out for the welfare of the community, especially from an economic and health point of view. The aim of this research is to describe how the implementation of the family planning program is carried out in the coastal area of Bagan Village, Percut Sei Tuan District, Deli Serdang Regency. This type of research is descriptive using a cross-sectional research design. The research was carried out in the coastal area of Bagan Percut Sei Tuan Village, Deli Serdang Regency in 2019. The sample in this study were PUS women in Bagan village, Percut Sei Tuan sub-district, a total of 44 people. Data was collected using a questionnaire.